Analisis Hukum dengan Ekonomi - Rusli, Hardijan (Pelita Harapan University, 2005)
Is the task of law aimed at increase of economic efficiency? The answer to this depends on the political tendency of the reader. For reader who are for market and economic liberal will certainly answer yes, while others who do not agree with this idea, especially those who are